2019
DOI: 10.1590/0104-6632.20190361s20170575
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis and Modeling of Brazilian Crude Oil and Asphaltene Systems: An Experimental Measurement and a Pc-Saft Application

Abstract: Asphaltenes represent the heaviest fraction of crude oils, being recognized by their tendency to self-associate and precipitate. Asphaltene precipitation and subsequent deposition can cause problems in all stages of production. The objective of this paper is to model Brazilian crude oil and asphaltene systems using the PC-SAFT equation of state. Asphaltenes were extracted from crude oil through the addition of different n-alkanes. The PC-SAFT was capable of accurately predicting liquid density for toluene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The common choice for A + R parameter tuning is BPs and crude oil densities [58]. Some authors [52,56,64,129] apply the n-alkane dilution onsets for the asphaltene parameter fitting, especially if asphaltenes are considered to be polydisperse [52,53,112].…”
Section: Saturates and Aromatics + Resins (A + R)mentioning
confidence: 99%
“…The common choice for A + R parameter tuning is BPs and crude oil densities [58]. Some authors [52,56,64,129] apply the n-alkane dilution onsets for the asphaltene parameter fitting, especially if asphaltenes are considered to be polydisperse [52,53,112].…”
Section: Saturates and Aromatics + Resins (A + R)mentioning
confidence: 99%
“…Tin, Hirasaki, and Chapman [36] showed that asphaltenes are unstable below a certain value of the oil solubility parameter, while Vargas et al found that the solubility parameter is not always constant along the stability boundary of asphaltenes.…”
Section: Solubility Approachmentioning
confidence: 99%
“…The equation is very versatile, and evidence of this is the number of different versions of the theory developed over the years. Although the differences may be small, the main symptom leading to different versions is the choice of a reference fluid [36].…”
Section: Statistical Associating Fluid Theory (Saft)mentioning
confidence: 99%
“…Morphological analysis showed that asphaltenes have well-defined granules, while natural kaolinite presents pseudo-hexagonal flat crystals in the form of lamellae with irregular borders. Asphaltenes are composed of about 1-10% heteroatoms (Andersen 1994) such as sulfur, oxygen, and nitrogen (Neuhaus et al 2019), of which sulfur usually has the highest concentration. This was confirmed by X-ray energy dispersion spectrometry (EDX) with 11.5%w/w and 4.1%w/w of sulfur and oxygen, respectively, and 84.4%w/w of carbon).…”
Section: Characterization Of Asphaltenes and Kaolinite Before The Adsmentioning
confidence: 99%
“…The asphaltene adsorption on the surface of clay minerals plays an important role in the oil industry: (i) altering the wettability, in which particles in contact with the crude oil change their hydrophobicity character; (ii) causing the fouling of the catalysts; and (iii) contaminating the bitumen, reducing the quality of the oil and hence generating higher costs (Dudášová et al 2008;Lucas et al 2009Lucas et al , 2015Nikakahtari et al 2013;Wang et al 2013;Osaky et al 2014;Maravilha and Spinelli, 2018;Neuhaus et al 2019). Although many researches have been done on tailing ponds treatment, this process still need to be improved (Nikakahtari et al 2013;Reis et al 2016;Vajihinejad et al 2017;Gumfekar and Soares 2018a, b;Vajihinejad and Soares 2018;Younes et al 2018).…”
Section: Introductionmentioning
confidence: 99%